2008
DOI: 10.1130/ges00122.1
|View full text |Cite
|
Sign up to set email alerts
|

Ash-flow tuffs and paleovalleys in northeastern Nevada: Implications for Eocene paleogeography and extension in the Sevier hinterland, northern Great Basin

Abstract: Northeastern Nevada is generally interpreted as an area of large-magnitude Eocene extension possibly due to gravitational collapse of crust thickened during the Sevier orogeny. The extensional interpretation is based in part on the presence of widespread Eocene conglomerates and lacustrine basins, as well as on thermochronology-based evidence of major Eocene cooling and uplift of the Ruby Mountains-East Humboldt Range core complex.The distribution of 45-40 Ma ash-fl ow tuffs and interbedded coarse conglomerate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

14
190
2

Year Published

2008
2008
2021
2021

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 130 publications
(206 citation statements)
references
References 82 publications
(154 reference statements)
14
190
2
Order By: Relevance
“…Results presented here support the thesis that basin development and lake hydrology in the Laramide foreland were characterized by large-scale changes in Cordilleran drainage patterns tapping distal source areas (DeCelles, 1994). Though drainage from the hinterland seems to have been the dominant pattern for much of the Paleogene (Fouch et al, 1983;Gierlowski-Kordesch et al, 2008;Henry, 2008), tectonically mediated drainage rearrangements within the foreland in some cases profoundly influenced the developing Laramide basins and their O isotope records. Unrecognized, such drainage rearrangements might easily confound studies of isotope paleoaltimetry.…”
supporting
confidence: 68%
“…Results presented here support the thesis that basin development and lake hydrology in the Laramide foreland were characterized by large-scale changes in Cordilleran drainage patterns tapping distal source areas (DeCelles, 1994). Though drainage from the hinterland seems to have been the dominant pattern for much of the Paleogene (Fouch et al, 1983;Gierlowski-Kordesch et al, 2008;Henry, 2008), tectonically mediated drainage rearrangements within the foreland in some cases profoundly influenced the developing Laramide basins and their O isotope records. Unrecognized, such drainage rearrangements might easily confound studies of isotope paleoaltimetry.…”
supporting
confidence: 68%
“…For example, in the northeastern Great Basin area, the Camilleri et al (1997) model states that the crust thinning was from 70 to 50 km by extensional unroofing between the Cretaceous and Eocene-Oligocene, whereas Constenius (1996) concluded that extensional basins formed from the middle Eocene to early Miocene. However, on the basis of his study of interbedded ash-flow tuffs and sedimentary deposits in northeastern Nevada, Henry (2008) concluded that Eocene extension was minor. The well-documented extreme extension found locally in core complexes in the eastern Great Basin (e.g.…”
Section: Previous Thoughts On Crustal Thickness Of the Great Basin Dumentioning
confidence: 99%
“…In contrast, recent work in the Eocene Caetano caldera at the north end of the Toiyabe Range ( fig. 2) also documented large-magnitude (approximately 100 percent strain) extension, but concluded that it took place in the middle Miocene (around 17-16 to 12-10 Ma), long after formation of the 34 Ma Caetano caldera (Colgan and others;2011, Colgan and others;2008, John and others;2008).…”
Section: Caldera Outline (Dashed Where Inferred)mentioning
confidence: 99%
“…Many of the ash-flow tuffs erupted from the calderas shown in figure 1 dispersed widely across the landscape by flowing along paleovalleys carved into the pre-Tertiary bedrock in the late Mesozoic or earlier in the Cenozoic (for example, Henry, 2008). Their distribution thus informs knowledge of regional topography prior to formation of the modern Basin and Range Province, when the region was thought to be a broad, high orogenic plateau, much of which drained to the Pacific Ocean (for example, DeCelles, 2004;Cassel and others, 2009;Henry and John, 2013).…”
Section: Caldera Outline (Dashed Where Inferred)mentioning
confidence: 99%
See 1 more Smart Citation